Enhancement of static magnetic field on biological hydrogen production via photo-fermentation of giant reed. (January 2023) - Shui, Xuenan; Jiang, Danping; Li, Yameng; Zhang, Huan; Yang, Jiabin; Zhang, Xueting; Zhang, Quanguo
Graphical abstract: Highlights: Static magnetic field was first employed in biological production. The highest bio-H2 yield achieved 112.7 mL/g TS with SMF at 20 mT. The SMF of 20 mT enhanced the activity of nitrogenase by 94.52%. SMF promoted the conversion of substrate to VFAs. Abstract: The effect of static magnetic field (SMF) on the system of photo-fermentation biological hydrogen production remains dimness. The goal of this study was to clarify the correlation between external SMF addition and hydrogen production via photo-fermentation from giant reed. SMF with 20 mT improved the cumulative H2 yield by 26.1% and reduced the lag time of hydrogen production by 56.7% compared with that of without external magnetic field. Moreover, 20 mT of SMF not only enhanced the activity of nitrogenase by 94.52%, but also obtained the maximum energy conversion efficiency of 27.27%. The distribution of volatile fatty acids proved that the concentration of acetic acid and butyric acid were 137% and 81% higher than that of without SMF, respectively. The results would help to trigger the positive interaction between SMF and microorganism and to avoid the possible negative interaction.